Microarray Profiling and Co-Expression Network Analysis of LncRNAs and mRNAs in Acute Respiratory Distress Syndrome Mouse Model - Xiaoling Wu; Chenjie Ma; Qinmei Ma; Peipei Zhuang; Guangcun Deng (Pathogens, 2022)
Background: Long noncoding RNAs (LncRNAs) play critical roles in many respiratory diseases. Acute respiratory distress syndrome (ARDS) is a destructive clinical syndrome of respiratory diseases. However, the potential mechanism of LncRNAs on ARDS remains largely unknown. Methods: To identify the profiles of LncRNAs and mRNAs in the LPS-induced ARDS mouse model, the microarray analyses were hired to detect the expression of LncRNAs and mRNAs in present study. Subsequently, microarray data were verified by quantitative qRT-PCR. Functional annotation on DE mRNAs and LncRNAs were carried out by bioinformatics analysis. Furthermore, the role of selected DE LncRNAs on correlated genes was confirmed by si-RNA and Western blot. Results: The expression of 2110 LncRNAs and 2690 mRNAs were significantly changed, which were further confirmed by qRT-PCR. GO and KEGG analysis indicated that the up-regulated mRNAs were mainly related to a defense response and tumor necrosis factor (TNF) signaling pathway, respectively. LncRNA-mRNA co-expression analyses showed that LncRNAs NR_003508, ENSMUST00000131638, ENSMUST00000119467, and ENSMUST00000124853 may correlate to MLKL, RIPK3, RIPK1, Caspase1, and NLRP3, respectively, or cooperatively, which were highly involved in the cell necroptosis process. Furthermore, siRNA for NR_003508 confirmed the co-expression analyses results. Conclusion: To summarize, this study implied that the DE LncRNAs could be potent regulators and target genes of ARDS and will provide a novel insight into the regulation of the pathogenesis of ARDS.